Family Awareness in Inheritance: Increasing Understanding of Islamic Inheritance Law in Society at the Kantor Urusan Agama (KUA) Tigaraksa District, Tangerang Regency - Bahrul Ulum; Renantha Meggy Putri (IRDH International Journal of Social Sciences & Humanities, 2025)
A seminar with the theme “Family Awareness in Inheritance: Improving Understanding of Islamic Inheritance Law in Society” was held in August 2025 at the Religious Affairs Office (KUA) of Tigaraksa District, Tangerang Regency, as part of the Independent Student Work Lecture (KKM) program of the Nahdlatul Ulama Islamic College (STiSNU). This activity was attended by 35 participants from various levels of society. The background to the implementation of this seminar was the still low understanding of some people regarding Islamic inheritance law, which often triggers problems and conflicts between families. The purpose of the seminar was to provide a comprehensive understanding of the concept, legal basis, and mechanism of inheritance distribution according to Islamic law, as well as to raise family awareness of the importance of justice and openness in the process. The methods used in the seminar included lectures, questions and answers, and case studies. The materials presented included: (1) the legal basis of Islamic inheritance based on the Qur'an and hadith, (2) the relationship between Islamic inheritance law and the Compilation of Islamic Law (KHI) in Indonesia, (3) identification of inheritance problems in society, and (4) strategies for building family awareness in resolving inheritance distribution. The seminar's results demonstrated the participants' high level of enthusiasm, evident in their active participation in the discussions and their increased understanding of the rights and obligations of heirs. The seminar concluded that increasing family awareness of Islamic inheritance law can minimize potential disputes, maintain family relationships, and ensure inheritance distribution in accordance with the principles of Islamic justice. It is hoped that similar activities can be conducted sustainably, involving more parties, to further enhance the spread of Islamic inheritance law literacy in society.